2011
DOI: 10.1007/s00228-011-1181-6
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicines use by Scottish women with breast cancer. What, why and the potential for drug interactions?

Abstract: The level of CAM use by Scottish breast cancer patients is similar to that reported from other countries, although there are marked differences in the type, nature and frequency of specific CAM therapies. Higher patient education level and use by family and friends were significantly associated with CAM use. The high level of use of potentially disease modifying or interacting herb supplements may be of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 43 publications
2
47
1
3
Order By: Relevance
“…At the same time, there is a fact of increasing rate of CAM use of patient with breast cancer. In the USA while health insurance system runs well, the CAM use was reported to 90% of the breast cancer patients and 44, 6% of those in Japan (Wong et al, 2010;McLay et al, 2012) From clinical perspective, it is important to identify factors that encourage large numbers of patients with breast cancer to use CAM, solely or concomitantly with conventional medical treatments, as breast cancer patients frequently face situations that are subjectively less controllable and more frightening than other chronic of life threatening disease. Previous studies suggested that the rate of CAM use depends on sociodemographic characteristics of patients, breast cancer related clinical characteristic, regional and cultural factors and patients pattern coping with the disease (Solner et al, 2000;Paltiel Few studies have also been conducted to examine the relationship between the unmet informational needs and the use of CAM in patients with breast cancer, although the topic of unmet needs has been a recurrent on in CAMrelated studies.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there is a fact of increasing rate of CAM use of patient with breast cancer. In the USA while health insurance system runs well, the CAM use was reported to 90% of the breast cancer patients and 44, 6% of those in Japan (Wong et al, 2010;McLay et al, 2012) From clinical perspective, it is important to identify factors that encourage large numbers of patients with breast cancer to use CAM, solely or concomitantly with conventional medical treatments, as breast cancer patients frequently face situations that are subjectively less controllable and more frightening than other chronic of life threatening disease. Previous studies suggested that the rate of CAM use depends on sociodemographic characteristics of patients, breast cancer related clinical characteristic, regional and cultural factors and patients pattern coping with the disease (Solner et al, 2000;Paltiel Few studies have also been conducted to examine the relationship between the unmet informational needs and the use of CAM in patients with breast cancer, although the topic of unmet needs has been a recurrent on in CAMrelated studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed disclosure of CAM use is critical for coordination of care and minimizing treatment conflicts [4]. However, estimates of CAM use disclosure to physicians vary widely depending on the population, but in general can be low ranging from 12 to 53 percent in oncology patients [5,6], 36 percent in HIV patients [7], and 21 to 71 percent in general medical populations [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A 'significant other' could be a spouse. A study investigating complementary alternative medicine use among women with a median of 4 years since breast cancer diagnosis reported 15 % more use of complementary alternative medicine (of which dietary supplement use is considered one) among their spouses v. women who were not using complementary alternative medicine themselves (8) . There are two reasons why understanding more about spouse concordance is important.…”
mentioning
confidence: 99%